ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2016 (Studi Kasus pada PT. Mayora Indah Tbk dan PT. Ultrajaya Milk Industry & Trading Company Tbk) - Riski Fajar Priananda; Abdul Wahid Mahsuni; Mohammad Amin (Universitas Islam Malang, 2018)
ABSTRACTThis research aims to know the financial performance of PT Mayora IndahTbk. And PT Ultrajaya Milk Industry & Trading Company Tbk in the period2013-2016 years. As well as knowing the financial performance comparisonbetween PT Mayora Indah Tbk and PT Ultrajaya Milk Industry & TradingCompany Tbk in the period 2013-2016. The population in this study were PTMayora and PT Ultrajaya, to find out the financial ratios that occur in 2013 to2016. In this study using sample data annual report PT Mayora and PT Ultrajayafor 4 years from the period 2013-2016. The method of analysis used in this studyis a method of ratio analysis, which covers the liquidity ratio, the ratio ofprofitability, solvency ratio, the ratio of the activity, the ratio of the market, aswell as different test (t test). Based on the results of the analysis of the differenttests can noted that there is a significant financial difference in performancebetween PT. Mayora Indah Tbk and PT Ultrajaya Milk Industry & TradingCompany Tbk in the period 2013-2016 views of Current Ratio (CR), , DER, DAR,Aged Accounts receivable. While the Quick Ratio (QR), Net Profit Margin (NPM),the Net Profit Margin (NPM), ROE, ROA, TATO, FATO, EPS, the EPR lackssignificant financial performance difference between PT. Mayora and PTUltrajaya.Keyword : liquidity ratio, profitability ratio, solvency ratio, activity ratio, ratio ofthe market